Description of a new species of Isagoras Stål (Phasmatodea: Pseudophasmatidae: Xerosomatinae: Prexaspini) from the State of Minas Gerais, Brazil - Heleodoro, Raphael Aquino; Rafael, José Albertino (Zootaxa, 2018)
Isagoras aurocaudata sp. nov. is being described from two female specimens from the States of Minas Gerais, Brazil. Diagnostic characters for the new species are the yellowish compound eye with brown spots, the yellowish spot at basal third of tegmina and the yellowish abdomen segments 8–11. Furthermore, Isagoras aurocaudata sp. nov. is compared to species of Isagoras Stål and Planudes Stål.